IMPLEMENTASI KEBIJAKAN PERCEPATAN PENCEGAHAN STUNTING TERINTEGRASI DI DESA PETIR KABUPATEN SERANG - Tiwi Rizkiyani; Ismayanti Ismayanti (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
Desa Petir is one of the stunting treatment locations in Kabupaten Serang. The prevalence of stunting in Desa Petir reached 63,8% by 2022 and is the village with the highest prevalence rate of stopping in Kabupaten Serang. Kabupaten Serang Government has issued the Regulations No. 40 of 2021 on Integrated Stunting Prevention Acceleration in Kabupaten Serang which forms the basis of policy as well as commitment in prevention efforts in the increasing number of stunting cases in Kabupaten Serang. This research aims to find out how the Stunting Prevention Acceleration Policy Implementation is integrated in Desa Petir Kabupaten Serang using the Edward III policy implementation model that is influenced by four variables, namely communication, resources, disposition, and bureaucratic structure. Research uses descriptive qualitative methods with data collection techniques such as observations, interviews, and documentation studies. Data analysis uses the analytical model developed by Miles and Huberman. The results of the research show that the implementation of the Integrated Stunting Prevention Acceleration Policy in Desa Petir Kabupaten Serang has not gone optimally because there are still some problems in its implementation. In terms of communication, the information delivered to the target group through socialization and dissemination has not been clearly transmitted. On the resource aspect, there are restrictions on Posyandu facilities. On the disposition aspect, preventive efforts are not made before the stunting case occurs. On the structural aspects of bureaucracy, there is frequent miscommunication between stakeholders at the village level, especially in the case of stunting. Keywords: Policy implementation, Stunting handling